Novel hole selective CrOx contact for dopant-free back contact silicon solar cells. (July 2018) - Lin, Wenjie; Wu, Weiliang; Bao, Jie; Liu, Zongtao; Qiu, Kaifu; Cai, Lun; Yao, Zhirong; Deng, Youjun; Liang, Zongcun; Shen, Hui
Graphical abstract: Highlights: The dopant-free back contact solar cells are demonstrated based on hole selective contact material, chromium trioxide (CrOx, x < 3) with a low melting point for high stability and high performance. CrOx is first applied in silicon based solar cell as the emitter. The back contact solar cell which demonstrated an efficiency of 15.8% and high stability was fabricated, by implementing the multilayer films of CrOx (5 nm)/Au (4 nm)/ CrOx (5 nm) capped by Ag (500 nm) as the emitter. Abstract: The dopant-free back contact solar cells are demonstrated based on hole selective contact material, chromium trioxide (CrOx, x < 3) with a low melting point for high stability and high performance. In this contribution, CrOx is first applied in silicon based solar cell as the emitter. Integrating 5 nm CrOx and 2 nm LiFx into solar cell as the emitter and the back surface filed, resulted in a device efficiency of 13.6%. For further improvement, the back contact solar cell reaching an efficiency of 15.8% was fabricated, by implementing the multilayer films of CrOx (5 nm)/Au (4 nm)/ CrOx (5 nm) as the emitter. The formation of Cr(OH)3 in ambient condition, resulted in a lower work function (4.8 eV) of the CrOx film. Furthermore, the multilayer back contact solar cell demonstrated a high stability due to CrOx covered with 500 nm Ag, when stored in ambient air longer than 170 days.